Faktor-Faktor yang Berhubungan dengan Kecemasan Menghadapi Masa Pubertas Remaja di SMPN 20 Kendari - La Ode Alifariki (Halu Oleo University, 2018)
ABSTRACTTeenage who have experienced puberty will experience a change both in physical or psychological. The changes that occur during puberty often cause anxiety. The purpose of this research was to know the factors related to anxiety facing teenage puberty at SMPN 20 Kendari. The type of this research was observational analytic research with cross sectional study approach. The research population were all students of class VIII and IX in SMPN 20 Kendari in the period of 2017 as many as 432 people. The sample of research were 81 respondents. The statistical test used is chi squre test. The results showed there was an association of self-acceptance with anxiety facing teenage puberty (X2hit) = 9,194> X2tab = 3.841, φ = 0.363). There was a parent-support relationship with anxiety facing teenage puberty (X2hit) = 5,506> X2tab = 3,841, φ = 0.287). There was a relationship of peer support with anxiety facing teenage puberty (X2hit) = 8.952> X2tab = 3,841, φ = 0.358). There was an association of students' knowledge with anxiety facing teenage puberty (X2hit) = 5,506> X2tab = 3,841, φ = 0,287).Keywords: Anxiety, Self Acceptance, Parental Support, Peer Support, Student Knowledge